Cara Mengurangi Dismenoare Pada Remaja Putri di SMK Putra Indonesia Malang - Baiq Yunia Harlin Indarti; Anita Faradilla Rahim (Jurnal Ventilator, 2023)
Counseling is carried out aimed at providing health information and education to adolescents about dysmenorrhea or pain during menstruation which can cause a teenager to be absent from school or other activities where dysmenorrhea is not a disease, but a symptom that arises due to abnormalities in the pelvic cavity and is very severe. Interfere with women's activities, even often requiring sufferers to rest or leave their work for hours due to dysmenorrhea. The method used is to provide information in the form of health promotion to adolescents by using posters as a medium in counseling, giving pre-test and also post-test in the form of questions to adolescents to measuring the effectiveness of the counseling that is being carried out. The extension went well so that in the evaluation there was a level of knowledge from the participants after being given counseling. Extension activities could increase the knowledge of adolescents about desminorrhea and how to reduce pain during menstruation.